Psychology and Religion: Two Approaches to Positive Mental Health - Haque, Amber (Intellectual Discourse, 2013)
Historically speaking, psychology and religion have worked separately toward the goal of improving mental health among the people. Can psychology and religion work together and reap better results for the client? How important is religion for the people and how important are religious values for psychologists? What is the relationship between religion and mental health? How today’s schools of psychology deal with the religious client? How is religion integrated in psychotherapy? These and other related issues are addressed in this paper. It is concluded that psychologists are obligated to work within the value system of the client and that this approach would achieve a more positive therapeutic outcome.